The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5433/1679-0359.2019v40n4p1427
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of pesticides used in peach orchards to eggs and pupae of the predators Chrysoperla externa and Coleomegilla quadrifasciata

Abstract: This study aimed to assess, under laboratory conditions, the selectivity of nine pesticides used in peach to the egg and pupal stages of the predators Chrysoperla externa and Coleomegilla quadrifasciata. Tests consisted of the direct application of pesticides on eggs and pupae of predators and assessment of sublethal effects on fertility and fecundity of emerged adults. For eggs, the pesticides were classified according to the effects on the reduction of the percentage of larval hatching, while for pupae they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The Chrysoperla externa species (Hagen, 1861) (Neuroptera: Chrysopidae) is commonly found in Brazil, with reports of occurrence in different regions [ 2 ]. Studies have shown the effectiveness of this predatory species in the biological control of pest arthropods (such as aphids and whiteflies), eggs and small caterpillars, as well as in field and controlled conditions for cotton, wheat, sorghum, citrus, peach and melon crops [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In addition to prey generalism, C. externa has aroused interest in biological control research due to the ease of its mass production in the laboratory and its environmental adaptability [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Chrysoperla externa species (Hagen, 1861) (Neuroptera: Chrysopidae) is commonly found in Brazil, with reports of occurrence in different regions [ 2 ]. Studies have shown the effectiveness of this predatory species in the biological control of pest arthropods (such as aphids and whiteflies), eggs and small caterpillars, as well as in field and controlled conditions for cotton, wheat, sorghum, citrus, peach and melon crops [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In addition to prey generalism, C. externa has aroused interest in biological control research due to the ease of its mass production in the laboratory and its environmental adaptability [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%